The correlation between radiographic knee OA and clinical symptoms—do we know everything?. Issue 11 (November 2015) - Herman, Amir; Chechik, Ofir; Segal, Ganit; Kosashvili, Yona; Lador, Ran; Salai, Moshe; Mor, Amit; Elbaz, Avi; Haim, Amir
Abstract This study aims to evaluate the correlations between common clinical osteoarthritis (OA) diagnostic tools in order to determine the value of each. A secondary goal was to investigate the influence of gender differences on the findings. Five hundred and eighteen patients with knee OA were evaluated using the Western Ontario and McMaster Osteoarthritis Index (WOMAC) questionnaire, short form 36 (SF-36) Health Survey, and plain radiographs. Analysis of variance (ANOVA) was used to compare the different domains of the WOMAC and SF-36 questionnaires between genders and the radiographic scale. Higher knee OA x-ray grade were associated with worse clinical outcome: for women, higher scores for the WOMAC pain, function and final scores and lower scores in the SF-36 final score; in men, lower SF-36 overall and physical domains scores. Gender differences were found in all clinical scores that were tested, with women having worse clinical scores for similar radiographic grading (p values <0.001). Knee radiographs for OA have an important role in the clinical evaluation of the patient. Patients with higher levels of knee OA in x-ray have a higher probability of having a worse clinical score in the WOMAC and SF-36 scores. The gender differences suggest that for similar knee OA x-ray grade, women's clinical scores are lower. Trial registration: NCT00767780